Toward an Effective Control of the H-2 to CO Ratio of Syngas through CO2 Electroreduction over Immobilized Gold Nanoparticles on Layered Titanate Nanosheets - Mota, Filipe Marques; Dang Le Tri Nguyen; Lee, Ji-Eun; Piao, Huiyan; Choy, Jin-Ho; Hwang, Yun Jeong; Kim, Dong Ha (AMER CHEMICAL SOC, 2018)
In recent years, the electroreduction of CO2 to valuable products has emerged as a rational answer to rising CO2 emissions and a strategic approach to incorporate renewable electricity from intermittent sources (e.g., wind and solar) into the global energy supply. The reduction of CO2 to CO has been highlighted in the widely explored industrial conversion of syngas (CO and H-2) to fuels. Herein, we report a promising electrocatalyst incorporating well-dispersed gold nanoparticles (Au NPs) on ultrathin titanate nanosheets (TiNS). By tuning the contents of Au (in the ranges of 0 to 93 wt % Au) in the hybrid Au/TiNS architecture, CO product selectivity was effectively controlled (in the range of CO Faradaic efficiency from 3 to over 80%) with the sole additional formation of H-2, which is of pronounced industrial interest. Most importantly, a control of both component amounts was suggested to result in a variation of corresponding electronic properties based on the interaction between Au NP and TiNS substrate, dictating the stabilization of formed reaction intermediates and resulting product selectivity. In addition, our Au/TiNS achieved optimally high CO and H-2 production current densities, with 73 wt % Au at the low cathodic potential region (-0.6 to -0.9 V-RHE). The suggested synergetic effect between both catalytic components underlines the promising character of this hybrid system and is expected to significantly add to the strategic production of syngas for subsequent applications.
Keywords: CARBON-DIOXIDE; ELECTROCHEMICAL REDUCTION; CATALYTIC-ACTIVITY; ELECTRO-REDUCTION; OXIDATION-STATE; DOPED TITANIA; SURFACE ATOMS; EFFICIENT; GAS; ELECTROCATALYST